THE EFFECT OF LEARNING MOTIVATION TOWARDS STUDENTS’ MATHEMATICS PROBLEM-SOLVING ABILITY: META-ANALYSIS CORRELATIONAL STUDY - Neza Zakiya Arili; Turmudi Turmudi; Dadan Dasari (Universitas Lambung Mangkurat, 2024)
Studies emphasize that learning motivation is one of the primary elements that affect the achievement of learning objectives and at the same time, influences the skill of mathematical problem-solving. Research on the correlation between mathematical problem-solving and learning motivation despite numerous attempts at solutions, the correlation value is heterogeneous, making it inconsistent. This study aims to summarize the effect-size values obtained based on the main research through the correlation meta-analysis method. The literature data collection technique used the Google Scholar database which was selected using the inclusion criteria. Primary studies that fit the criteria consisted of 20 studies published in journals, proceedings, and theses from 2016 to 2022. Three steps of data analysis, including publication bias research, random or fixed effect models, and statistical hypothesis testing, were conducted using the Jeffreys Amazing Statistics Program (JASP) program. The results of the study show that there is a positive influence of learning motivation on students' mathematical problem-solving abilities at the elementary, middle, and high school levels in Indonesia in the moderate category (r = 0,56; p < 0,01). The results of this study suggest educators to further optimize students' learning motivation because learning motivation influences the level of students' mathematical problem-solving ability. Keywords: Learning motivation, mathematical problem-solving, problem-solving, meta-analysis